Transforming noun phrase structure form into heuristics and rules for detecting compound noun in Malay sentence - Ab. Rahman, Suhaimi; Omar, Nazlia (2012)
This paper addresses the process of transforming noun phrase structure form into a list of suitable heuristic used for detecting compound noun word in Malay sentence.The heuristic is used to obtain the syntax sentence structure for finding a compound noun pair of words in Malay sentence. To obtain the list of these rules, the noun phrase structure form must be created first, so that we know the possibility of the words' combination as a compound noun.The noun phrase structure form is grouped based on three different noun categories, such as i) noun and noun ii) noun and noun modifier, and iii) noun and non-noun modifier.However, in our research work, we focus on the category of noun and noun modifier.The heuristic rules and noun phrase structure form are important to understand because they help to clarify the concept of finding compound noun pair of words in Malay sentence.This compound noun output will use an input in our next research named head modifier detector.